2018
DOI: 10.1002/jcb.26898
|View full text |Cite
|
Sign up to set email alerts
|

Metformin increases the cytotoxicity of oxaliplatin in human DLD‐1 colorectal cancer cells through down‐regulating HMGB1 expression

Abstract: Colorectal cancer (CRC) is the fourth most common cause of cancer death worldwide. Chemotherapy has been the major strategy for treating patients with advanced CRC. Oxaliplatin (OXA) is used as both an adjuvant and neoadjuvant anticancer agent available to treat advanced CRC. High-mobility group box 1 protein (HMGB1) is a critical regulator of cell death and survival. HMGB1 overexpression has been shown to be resistant to cytotoxic agents. In addition, Metformin, a widely used drug for diabetes, has emerged as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In addition, HMGB1 has been identified as an autophagy sensor in oxidative stress [30], and autophagy may regulate the expression and release of HMGB1 [31]. However, increasing evidences indicates that HMGB1 is downregulated by metformin [23]. In our previous studies, we found that metformin induced autophagy by activating AMPK, resulting in decreased proliferation and migration of endothelial progenitor cells [32,33].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, HMGB1 has been identified as an autophagy sensor in oxidative stress [30], and autophagy may regulate the expression and release of HMGB1 [31]. However, increasing evidences indicates that HMGB1 is downregulated by metformin [23]. In our previous studies, we found that metformin induced autophagy by activating AMPK, resulting in decreased proliferation and migration of endothelial progenitor cells [32,33].…”
Section: Discussionmentioning
confidence: 96%
“…Metformin's promotion of microRNA expression and anti-inflammatory effects also contribute to this process [19][20][21]. In prior studies, metformin was found to inhibit the expression and release of HMGB1 [22,23]. We therefore speculated that metformin may inhibit high glucose-induced VSMC proliferation and migration via microRNA-mediated inhibition of HMGB1 expression.…”
Section: Agingmentioning
confidence: 99%
“…Both 1,25D3 and metformin synergistically promotes apoptosis, and autophagy irrespective of the p53 status in all of the cells tested via AMPK, intracellular ROS, Bcl-2, and increasing LC3II:LC3I ratio. Additionally, metformin addition in the combination treatment arrests cell cycle in G 2 /M phase (HCT116 p53 − / − ) and S phase (HT-29 cells).[43]In a different report, metformin at 1 mM (24 h) increases the sensitization of HT29 cells to oxaliplatin (R = 2.66, P < 0.01) but no in HCT116 cells[46]DLD-1 cellsMetformin (5 mM, 24 h) synergistically promotes oxaliplatin (12.5 μM) cytotoxic and anti-proliferative b increasing HMGB1 expression via Akt and ERK1/2.Metformin activates AMPK signaling at lower concentration and short time exposure (0.5–2 μM, 1 h) prior to radiation leads to radioresistance.[49, 54]SW-480 and HT-29Pretreatment with metformin (2 mM, 16 h) activates AMPK signaling that inhibits the phosphorylation of β-catenin and Akt (Ser473) induced by insulin (10 ng/mL)or IGF-1 (10 ng/mL).[51]HCT116, RKO and HT-29 cellsMetformin (1 and 5 mM, 24 h) did not inhibit the proliferation and daily treatment (5 mM, 2 weeks) did not suppress the anchorage-independent growth, apoptosis, autophagy, and cell cycle arrest.[53]…”
Section: The Preclinical Evidence Use Of Metformin In Crcmentioning
confidence: 99%
“…Other than enhancing the effect of chemotherapeutic drugs, metformin also potentiates the adjuvant activity in CRC models. Metformin (5 mM, 24 h) synergistically promotes oxaliplatin (12.5 μM) cytotoxic and anti-proliferative effects in DLD-1 cells [49]. The single treatment with oxaliplatin (2.5–25 μM, 1–24 h) in DLD-1 cells promotes the expression of high-mobility group box 1 protein (HMGB1) via Akt and ERK1/2 that induces chemoresistant against chemotherapeutic drugs.…”
Section: The Preclinical Evidence Use Of Metformin In Crcmentioning
confidence: 99%
“…In human gastric and esophageal cancer cell lines and in xenograft mouse models, MTF combined with 2DG sufficiently inhibited energy pathways, resulting in significant cell death accompanied with decreased cellular ATP, prolonged AMPK activation, and support of autophagy [ 106 ]. In colorectal cancer cells, oxaliplatin combined with MTF resulted in synergistic cytotoxicity, and limited expression of high mobility group box 1 (HMGB1), which is a regulator of cell death and survival [ 107 ]. In triple-negative breast cancer cells that were resistant to programmed cell death induced by extracellular matrix detachment (anoikis), the effect of combined treatment of MTF with 2DG was more pronounced to suppress proliferation and induce detachment of cells compared to single drug applications [ 108 ].…”
Section: Pleiotropic Mtf Effects On Cancer: Basic and Preclinical mentioning
confidence: 99%